You ask (Journal of Parents and Teachers, 2025)
The article is divided into two sections, featuring two central questions that generate a debate for discussion. The first addresses austerity as an objective or a strategy. In the second part, there is a testimony from some parents who express that their children are continuously insulting others and ask what they can do to stop this situation.
Keywords: quest; austerity; objectives; strategy